2004
DOI: 10.1677/jme.0.0320975
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the estrogen regulation of the zebrafish estrogen receptor (ER) reveals distinct effects of ERalpha, ERbeta1 and ERbeta2

Abstract: We have previously cloned and characterized three estrogen receptors (ER) in the zebrafish (zfERalpha, zfERbeta1 and zfERbeta2). We have also shown that they are functional in vitro and exhibit a distinct expression pattern, although partially overlapping, in the brain of zebrafish. In this paper, we have shown that the hepatic expression of these zfER genes responds differently to estradiol (E2). In fact, a 48-h direct exposure of zebrafish to E2 resulted in a strong stimulation of zfERalpha gene expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 45 publications
(51 reference statements)
16
101
1
1
Order By: Relevance
“…It has been shown that ERα plays a dominant role in the up-regulation of Vtg mRNA expression in the liver of female mosquitofish (Huang et al, 2012) and other fish (Sabo-Attwood et al, 2004;Davis et al, 2007) by E2. The lack of significant changes found in ERβ mRNA expression levels in the liver of male mosquitofish in response to E2 is consistent with other studies in which E2 treatment had no effects on zebrafish (Menuet et al, 2004) and male goldfish (Pomatto et al, 2011), suggesting that ERβ is unlikely to be the primary mediator of E2 actions on the liver associated with the induction of Vtg mRNA expression. It has been previously shown that the presence of an estrogen-responsive element (ERE) in the promoter of ERα in the rainbow trout may be a major cis-acting element involved in the regulation of the gene by E2 (Le Dréan et al, 1995).…”
Section: Effects Of Steroid Hormones On Er Gene Expressionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been shown that ERα plays a dominant role in the up-regulation of Vtg mRNA expression in the liver of female mosquitofish (Huang et al, 2012) and other fish (Sabo-Attwood et al, 2004;Davis et al, 2007) by E2. The lack of significant changes found in ERβ mRNA expression levels in the liver of male mosquitofish in response to E2 is consistent with other studies in which E2 treatment had no effects on zebrafish (Menuet et al, 2004) and male goldfish (Pomatto et al, 2011), suggesting that ERβ is unlikely to be the primary mediator of E2 actions on the liver associated with the induction of Vtg mRNA expression. It has been previously shown that the presence of an estrogen-responsive element (ERE) in the promoter of ERα in the rainbow trout may be a major cis-acting element involved in the regulation of the gene by E2 (Le Dréan et al, 1995).…”
Section: Effects Of Steroid Hormones On Er Gene Expressionsupporting
confidence: 90%
“…It has been previously shown that the presence of an estrogen-responsive element (ERE) in the promoter of ERα in the rainbow trout may be a major cis-acting element involved in the regulation of the gene by E2 (Le Dréan et al, 1995). In addition, an imperfect ERE in the promoter of ERα has been demonstrated in the zebrafish along with ERE half sites with no consensus EREs in the promoter of ERβ (Lassiter et al, 2002;Menuet et al, 2004). It is still unclear whether the presence of different EREs in the promoters of different ER genes instructs their response to E2.…”
Section: Effects Of Steroid Hormones On Er Gene Expressionmentioning
confidence: 99%
“…Accompanying the decrease in blood E 2 was a decrease in ER␣ mRNA levels in the goldfish hypothalamus and telencephalon. The promoter of the teleost ER␣ contains one full estrogen response element (ERE) and one half-ERE, which have been shown to contribute to E 2 -stimulated ER␣ expression in vitro (37). Therefore, the decrease in circulating E 2 may have resulted in the decreased transcription of ER␣ observed in our study.…”
Section: Fluoxetine Reduces Plasma E 2 and Changes Expression Of Er Imentioning
confidence: 64%
“…Males and females were treated with E2 (1 μg/l), which binds to all zebrafish estrogen receptors (Menuet et al, 2004). After 16 dot, no changes are observed in the intact and regenerating female pectoral fins (n=6; Fig.…”
Section: Research Articlementioning
confidence: 99%